2017
DOI: 10.1128/aem.02641-16
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Polyesterases from Moss-Associated Microorganisms

Abstract: The growing pollution of the environment with plastic debris is a global threat which urgently requires biotechnological solutions. Enzymatic recycling not only prevents pollution but also would allow recovery of valuable building blocks. Therefore, we explored the existence of microbial polyesterases in microbial communities associated with the Sphagnum magellanicum moss, a key species within unexploited bog ecosystems. This resulted in the identification of six novel esterases, which were isolated, cloned, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The monomer Ta represented the most abundant compound detected at all experimental conditions and was proven not to be metabolised by the organism. This suggests the involvement of the fungus extracellular enzymes in the cleavage of aromatic ester bonds present in PBAT chains 17,45 , which are reportedly less prone to hydrolysis than the ester bond with aliphatic monomer (adipic acid) as also described for P. pseudoalcaligenes polyesterase PpEst 15 . Previous studies on single enzyme hydrolysis process of milled PBAT reported that BTaB and BTa were more abundant than the monomer, as well as that an increase of Ta concentration is given by higher pH than that selected in the current study 7 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The monomer Ta represented the most abundant compound detected at all experimental conditions and was proven not to be metabolised by the organism. This suggests the involvement of the fungus extracellular enzymes in the cleavage of aromatic ester bonds present in PBAT chains 17,45 , which are reportedly less prone to hydrolysis than the ester bond with aliphatic monomer (adipic acid) as also described for P. pseudoalcaligenes polyesterase PpEst 15 . Previous studies on single enzyme hydrolysis process of milled PBAT reported that BTaB and BTa were more abundant than the monomer, as well as that an increase of Ta concentration is given by higher pH than that selected in the current study 7 .…”
Section: Discussionmentioning
confidence: 57%
“…bation with PBAT, the supernatants were diluted with ice-cold methanol (1:1 v/v) in order to precipitate the enzymes and acidified to pH 3.0 with 1 M HCl. The samples were centrifuged at 18.213 x g (5427 R, Eppendorf) for 15 min at 4 °C, then filtered through 0.45 μm nylon syringe filters and thereafter analysed by a HPLC-DAD system consisting of a 1290 Infinity II LC (Agilent Technologies), coupled with a reversed phase column C18 (Poroshell 120 EC-C18 2,7 µm 3.0 × 150 mm), at a flow rate of 0.4 mL/min 15,19 . The PBAT hydrolysis products were separated using a nonlinear gradient according to Quartinello et al 2 with some modifications (i.e.…”
Section: Analysis Of Molecules Released From Pbat During Exposure Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The 3.6 Gbps metagenomic fosmid library was established in E. coli EPI300 pCC2FOS (Epicentre, Wisconsin, USA), incorporating ~40 kb metagenomic DNA from the Alpine peat bog moss S. magellanicum as previously described 55 . The generated 90 000 metagenomic clones were pooled by resuspending them in LB medium supplied with 20% glycerol for long term storage at −70°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, lipolytic enzymes clustering within other families (Arpigny and Jaeger, ), e.g. family VIII (β‐lactamase like), were likewise associated with polyesterase activity very recently (Biundo et al ., ; Müller et al ., ; Hajighasemi et al ., ). Besides biodegradation of artificial polyesters like PET, cutinases/polyesterases are discussed for different biotechnological applications, e.g.…”
Section: Introductionmentioning
confidence: 99%